Overview of Psychological Well-Being After The Flood Disaster in Meteseh Village Semarang City - Ani Fatur Rohmah; Ni Made Ayu Wulan Sari; Prita Adisty Handayani (NERSI: Jurnal Keperawatan Indonesia, 2025)
A disaster is an event or incident caused by natural or human factors, resulting in human casualties, environmental damage, property loss, and psychological impacts on disaster victims. One such disaster is flooding. This study aims to describe  psychological well-being after a flood disaster. This study used descriptive analysis techniques, with a sample size of 105 respondents using purposive sampling. The study was conducted over 21 days from May 11 to May 31. The measurement tool used was a Psychological Well-Being scale questionnaire. Data analysis was performed using univariate analysis with frequency distribution tables. The results of this study showed that 34 respondents or 32.4% had moderate psychological well-being. Based on this study, it is hoped that the scope of research can be expanded to be more complete and useful. This study recommends that psychological well-being be included in disaster nursing studies and as a basis for disaster nursing interventions. Keywords: disaster, flood, psychological well-being